The 65 and 110 kDa SR-related proteins of the U4/U6⋅U5 tri-snRNP are essential for the assembly of mature spliceosomes - Makarova, Olga V. (Oxford University Press, 2001)
The association of the U4/U6⋅U5 tri-snRNP with pre-spliceosomes is a poorly understood step in the spliceosome assembly pathway. We have identified two human tri-snRNP proteins (of 65 and 110 kDa) that play an essential role in this process. Characterization by cDNA cloning of the 65 and 110 kDa proteins revealed that they are likely orthologues of the yeast spliceosomal proteins Sad1p and Snu66p, respectively. Immunodepletion of either protein from the HeLa cell nuclear extracts inhibited pre-mRNA splicing due to a block in the formation of mature spliceosomes, but had no effect on the integrity of the U4/U6⋅U5 tri-snRNP. Spliceosome assembly and splicing catalysis could be restored to the respective depleted extract by the addition of recombinant 65 or 110 kDa protein. Our data demonstrate that both proteins are essential for the recruitment of the tri-snRNP to the pre-spliceosome but not for the maintenance of the tri-snRNP stability. Moreover, since both proteins contain an N-terminal RS domain, they could mediate the association of the tri-snRNP with pre-spliceosomes by interaction with members of the SR protein family.